Television / The Critical View Fifth Edition - Newcomb Horace (Oxford University Press, 1994)
The preeminent collection of contemporary academic television criticism. Television and the Present Climate of Criticism, The Production Contexts of Television, Television Texts, The Reception Contexts of Television, Overviews, About the Authors.